Student’s Personalities on Speaking Achievement in English Education Department:: A Comparative Study between Extroverted and Introverted. - Maemunah Maemunah; Hanif Nurcholish Adiantika; Dila Charisma (National Conference on Language, Education, and Technology Proceeding, 2022)
Abstract: The aim of this research is to find out if is there a significant difference between students with extrovert and introvert personalities speaking achievement in English Education Department. The design of this study was quantitative comparative research method. The population of this research was the English Students Department at Universitas Muhammadiyah Cirebon, and the sample of this research was the Fourth and Second Semesters. The instruments of the study were questionnaire and assignment In analyzing the data of the study, the researcher used Independent sample T-test in SPSS 26.0 for windows. In this study, the Independent Sample T-test was showed the value of Sig.(2-tailed) = 0.133 > 0.05. This means that the sig (2-tailed) value is higher than 0.05. And the result of the T-table was t value is 1,603 < the table t value is 2,228. This means the t value is lower than the t table. Based on the T-test and T-table, can be concluded that there is no significant differences between students with extroverted and introverted personality in speaking achievement. This study showed that there is no significant difference in speaking achievement between students with extroverted and introverted personalities.